find the answer by using quadratic formula method
Attachments:
![](https://hi-static.z-dn.net/files/d86/17c84162ce2836b2760e2489e0758c52.jpg)
Answers
Answered by
3
☯ Answer ☯
╭☞ I think Question is like this, √2x² + 7x + 5√2 = 0
╭☞ so now, √2x² + 7x + 5√2 = 0
╭☞ √2X² + 7X + 5√2 = 0
╭☞ (√2X² ) + ( 2X + 5X ) + ( 5√2 ) = 0
╭☞ (√2 × X² ) + (√2 × √2 × X ) + ( 5 × X ) + ( 5 × √2 ) = 0
╭☞ √2X ( X + √2 ) + 5 ( X + √2 ) = 0
╭☞ ( √2X + 5 ) ( X + √2 ) = 0
╭☞ √2X + 5 = 0 OR X + √2 = 0
╭☞ √2X = – 5 OR X = – √2
╭☞ X = – 5 OR X = – √2
√2
I Hope it helps you.
Similar questions